2018
DOI: 10.1523/jneurosci.2518-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and Divergence of CRH Amacrine Cells in Mouse Retinal Circuitry

Abstract: Inhibitory interneurons sculpt the outputs of excitatory circuits to expand the dynamic range of information processing. In mammalian retina, >30 types of amacrine cells provide lateral inhibition to vertical, excitatory bipolar cell circuits, but functional roles for only a few amacrine cells are well established. Here, we elucidate the function of corticotropin-releasing hormone (CRH)-expressing amacrine cells labeled in Cre-transgenic mice of either sex. CRH cells costratify with the ON alpha ganglion cell,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 83 publications
5
65
0
Order By: Relevance
“…6b, right), and was smaller than the center size measured during the Off-phase (~180µm). A similar difference is apparent in a previous study (Park et al, 2018).…”
Section: S3-and S5-gbx2+ Acs Cells Receive Center and Surround Inhibisupporting
confidence: 87%
See 2 more Smart Citations
“…6b, right), and was smaller than the center size measured during the Off-phase (~180µm). A similar difference is apparent in a previous study (Park et al, 2018).…”
Section: S3-and S5-gbx2+ Acs Cells Receive Center and Surround Inhibisupporting
confidence: 87%
“…S5-Gbx2+ ACs also share morphological, molecular, and physiological properties with the previously described CRH-1 AC (Zhu et al, 2014;Jacoby et al, 2015;Park et al, 2018). S5-Gbx2+ ACs and CRH-1 ACs have dendritic arbors of a similar size and shape that stratify in S5 of the IPL, they both express the neuropeptide Crh (corticotrophin-releasing hormone), and have similar physiological properties in response to ON light stimuli (Jacoby et al, 2015;Park et al, 2018). The CRH-IRES-Cre line used in these studies labels at least three different AC subtypes, which can be distinguished based on their morphological differences.…”
Section: Categorization Of Amacrine Cell Subtypessupporting
confidence: 58%
See 1 more Smart Citation
“…al, 2011), VG3 ACs (C13: VGlut3 [Slc17a8]; Haverkamp and Wässle, 2004;Johnson et al, 2004;Krishnaswamy et al, 2015); and A17 ACs (C6: Prkca (PKCα), Sdk1, Calb2 negative, Dab1-negative; Grimes et al, 2010;Puthussery and Fletcher 2007;Yamagata and Sanes, 2019). Other types expressed neuropeptides known to mark specific AC types; they include Cck (C10,C17,C18,C34; Firth et al, 2002), Vip, (C22,C26,C47; Park et al, 2015;Akrouh and Kerschensteiner, 2015;Pérez de Sevilla Müller et al, 2019), Crh (C37; Park et al, 2018) and Penk (C35,C59,C63; Chen et al, 2013). For some of these types, we were able to validate new markers, such as Car3 for VG3 cells (Figure 3B,C).…”
Section: Correspondence Between Clusters and Ac Typesmentioning
confidence: 86%
“…The NOS-1 cell was described also as the CRH-2 cell (Corticotropin-releasing hormone AC-2) based on labeling in the CRH-ires-Cre retina (Zhu et al, 2014). We, however, found that Cre-expressing cells in the CRH-ires-Cre::Ai32 retina are rarely labeled by the nNOS antibody (Park et al, 2018), suggesting limited overlap in CRH+ and NOS+ AC populations. Indeed, we found no co-expression of CRH and NOS by immunohistochemistry (P12 retina) (n = 66 CRH+ cells and 85 NOS+ cells, one retina) in neurons in the GCL (Figure 6E-G).…”
Section: Resultsmentioning
confidence: 83%